Business Support Within Business Incubators - Ratinho, Tiago; Harms, Rainer; Groen, Aard J. (University of Twente, 2009)
Business incubators (BI) have been established worldwide as tools for company creation and small businesses support. BIs claim to help their tenants by providing them with the optimal conditions for increasing early stage survival. Practitioners and researchers agree that business support is a crucial dimension of BI. Yet this feature is seldom researched. In this study we investigate to what extent business incubators support their tenants overcome their developmental problems. Results show that tenants do not experience many problems and when they do business support is not necessarily sought. Furthermore, our data suggests that business support is not preferentially sought within incubator environment. When this happens, support provided by the BI does not contribute to problem solving. Finally, we discuss the impact of the type of BI in helping their tenants.
Keywords: business support; business incubators; business incubation; business support; problem solving